THE ROLE OF INDONESIAN MEDICAL DISCIPLINARY BOARD’S VERDICT ON MEDICAL DISCIPLINARY VIOLATION IN MEDICAL DISPUTES SETTLEMENT - Nayla - Alawiya (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Whether there is medical disciplinary violation or not is decided by Indonesian Medical Disciplinary Board (MKDKI) according to the mandate of Article 55 of Law Number 29 Year 2004 on Medical Practice. Article 66 paragraph (3) of Law Number 29 Year 2004 also grants right for every person whose interest are violated by a doctor or dentist’s act during their medical practice to report the alleged criminal offense to the authority or file a civil lawsuit to court. The provision potentially weakens MKDKI’s verdict role in medical dispute settlement. The result shows that MKDKI in medical dispute settlement contribute to provide written real evidence. It can be medical dispute settlement by mediation, a report to the authority or a suit to court. The role of MKDKI’s verdict is still hampered by several factors including law, law enforcement, facilities and cultural factors. Keywords: Medical Dispute; Doctors and Dentists; Disciplinary violations; MKDKI; The verdict role.